Kepemimpinan Kepala Cabang Dinas dalam Peningkatan Kinerja Pegawai pada Dinas Pendidikan Kabupaten Pangkep - Nonarming, Nonarming; Rahman, Rahman; Hasran, Hasran (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2023)
This research aims to evaluate the leadership role of the Head of Service in increasing employee performance motivation at the Pangkep Regency Education Office and analyze the factors that influence this leadership. The approach used is descriptive qualitative, with data collection techniques through observation, in-depth interviews and literature study. The research results show that the leadership of the Head of Service at the Pangkep Regency Education Service is reflected in the level of employee involvement in program planning, a moderate level of communication, consistent giving of rewards, low levels of punishment, and moderate supervision of employee activities. Factors that influence the leadership of the Head of Service include the level of education, experience, authority, and aspects of heredity. However, the majority of respondents considered that hereditary factors did not have a significant influence on the leadership of the Head of the Pangkep Regency Education Service.